Dysfunction of B Cell Leading to Failure of Immunoglobulin Response Is Ameliorated by Dietary Silk Peptide in 14-Month-Old C57BL/6 Mice - Chei, Sungwoo; Oh, Hyun-Ji; Lee, Kippeum; Jin, Heegu; Lee, Jeong-Yong; Lee, Boo-Yong (Frontiers in Nutrition, 2020)
Anti-aging research suggests that immunosenescent cells can play deleterious roles in the immune system. Here, young (2 months old) and old (14 months old) C57BL/6 mice received a daily oral dose (100 or 750 mg/kg/day) of acid-hydrolyzed silk peptide (SP) for a period of 5 weeks. Mice spleen, lymph node, and serum were analyzed to determine the immune homeostasis of SP by flow cytometry, western blotting, ELISA, and qRT-PCR. The results suggest that SP ameliorates age-related dysfunction of T and B cells. Amelioration of B cell dysfunction improved the immunoglobulin response in aged mice. Taken together, the results suggest that SP restores immune homeostasis with respect to immunosenescent cells.